Pengaruh Likuiditas, Solvabilitas, dan Profitabilitas terhadap Nilai Perusahaan Sektor Consumer Goods yang Terdaftar di Bursa Efek Indonesia - Muhammad Abduh Hafidz; Agrianti Komalasari; Yuztitya Asmaranti; Neny Desriani (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2025)
Company value is one of the main indicators used by investors to assess the performance and prospects of a company. This study aims to analyze the influence of liquidity, solvency, and profitability on the value of consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The research sample consisted of 20 companies selected using the purposive sampling method. Data analysis was carried out by multiple linear regression using SPSS 27 software. The results show that liquidity has a negative and significant effect on company value, solvency has a positive and significant effect on company value, while profitability does not have a significant effect on company value. These results indicate that management must pay attention to efficiency in managing liquid assets, maintain a balance between debt and its own capital, and consider other factors other than profitability in increasing company value.